2018
DOI: 10.1007/s00382-018-4306-0
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of interannual temperature variability

Abstract: Energetics of interannual temperature variability in the years 1980-2016 is studied using two reanalysis data sets. Monthly temperature anomalies are decomposed to contributions from the net surface energy flux, atmospheric energy convergence minus storage (CONV), and processes that affect the top-of-the-atmosphere radiation balance. The analysis reveals a strong compensation between the net surface heat flux and CONV over the ice-free oceans, with the former driving the temperature variability over the tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Wintertime temperature conditions are likewise affected by ice conditions in the nearby Baltic Sea and snow cover through their albedo and thermal insulation capacity (Vavrus, 2007). Correspondingly, summer temperatures are influenced by soil moisture through the latent heat flux of evapotranspiration (Seneviratne et al ., 2010) and cloudiness (Räisänen, 2019b). These factors partly explain the coincidence of a high SLP and temperature in summer (Figure 2), since anticyclonic weather conditions tend to be clear and dry.…”
Section: Discussionmentioning
confidence: 99%
“…Wintertime temperature conditions are likewise affected by ice conditions in the nearby Baltic Sea and snow cover through their albedo and thermal insulation capacity (Vavrus, 2007). Correspondingly, summer temperatures are influenced by soil moisture through the latent heat flux of evapotranspiration (Seneviratne et al ., 2010) and cloudiness (Räisänen, 2019b). These factors partly explain the coincidence of a high SLP and temperature in summer (Figure 2), since anticyclonic weather conditions tend to be clear and dry.…”
Section: Discussionmentioning
confidence: 99%
“…This heatwave was therefore most likely driven by an increase in incoming solar radiation allowed by unusually clear skies (cf. Räisänen, , who found that variations in the short‐wave cloud forcing – i.e. how clouds affect the amount of solar radiation reaching the surface – drive much of the temperature variability in mid‐latitude land areas in summer).…”
Section: Discussionmentioning
confidence: 99%
“…This is important, as extended periods with warm conditions have a stronger impact on human health as well as on other parts of nature than a single heat day (e.g. Oudin Åström et al, 2013;Rasmont and Iserbyt, 2012). Figure 4d shows the time series for max_conWarmD where the thin coloured lines represent the single ensemble members, the bold lines represent the ensemble means, and the horizontal dotted black line indicates the max_conWarmD value of 2018 as calculated from E-OBS.…”
Section: How Extreme Was the Warm Summer Of 2018 Inmentioning
confidence: 99%
“…Heatwaves are also reported to have impacted Sweden prior to 2018 in terms of an increased mortality rate among people (e.g. Oudin Åström et al, 2013), ecological consequences (Rasmont and Iserbyt, 2012), and in connection with air pollution episodes (Struzewska and Kaminski, 2008).…”
Section: Introductionmentioning
confidence: 99%